Effects of pelleting and pellet conditioning temperatures on weanling pig performance - M U Steidinger; Michael D Tokach; P R O'Quinn; J C Woodworth; Leland J McKinney; B S Borg; J M Campbell; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
Two studies were conducted to evaluate" the effects of pelleting and pellet conditioning temperature of diets containing 5% spray-dried animal plasma (SDAP) on weanling pig growth performance. In Exp. 1, conditioning temperatures evaluated were 140, 150, 160, and 170°F. In Exp. 2, pellet conditioning temperatures were 140, 155, 170, 185, and 200°F. The results suggest that pellet conditioning temperatures above 170°F decrease weanling pig performance from d 0 to 7 after weaning. Pellet conditioning temperature should not exceed 170OF (exit temperature of 180°F) for nursery diets containing 5% SDAP.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Weanling pigs; Spray-dried animal plasma; Pellet conditioning termperature